Ensuring efficient development of personalized medicine by addressing regulatory needs: What role can research infrastructures play?. Issue 2 (June 2023) - Capone, Francesca; Morrow, David; Moretti, Franca
Personalized Medicine is a novel medical practice that uses an individual's genetic profile to guide decisions made regarding the prevention, diagnosis, and treatment of disease. Knowledge of a patient's genetic profile is crucial to support doctors in selecting the proper therapy and administer it using the correct dose or regimen. Personalized Medicine is a great opportunity to turn the "one size fits all" approach to diagnostics, therapy, and prevention, into an individualized approach. In this paper we analyze the most recent achievements and regulatory challenges in Personalized Medicine and the role that research infrastructures can play in advancing its development.